2020
DOI: 10.1016/j.athoracsur.2019.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Access Versus Sternotomy for Complex Mitral Valve Repair: A Meta-Analysis

Abstract: Background. There is high demand for minimally invasive mitral valve repair; however, it is unclear whether the minimally invasive approach provides the same performance as conventional sternotomy in a context of complex mitral valve disease. Here, we compared outcomes of minimally invasive and sternotomy procedures for bileaflet and Barlow's mitral valve disease.Methods. We performed a pooled meta-analysis of studies reporting early and late follow-up of mitral valve repair for complex mitral valve regurgitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
5
43
0
Order By: Relevance
“…According to the Phan et al Bayesian network meta-analysis, the right mini-thoracotomy approach for aortic valve replacement (AVR) was associated to a significantly increased CPB and cross-clamp time compared to sternotomy approach (P=0.001) (17). The same applies to minimally invasive mitral procedures; in a recently published meta-analysis by Moscarelli et al including 1,905 patients, minimally invasive mitral valve surgery was associated with a mean 32 mins of additional CPB duration (P<0.01) compared to sternotomy approach (18). Even in totally endoscopic CABG (TECAB) the current trend favors implementation of CPB (19,20) rather than operating off-pump.…”
Section: Rationalementioning
confidence: 99%
“…According to the Phan et al Bayesian network meta-analysis, the right mini-thoracotomy approach for aortic valve replacement (AVR) was associated to a significantly increased CPB and cross-clamp time compared to sternotomy approach (P=0.001) (17). The same applies to minimally invasive mitral procedures; in a recently published meta-analysis by Moscarelli et al including 1,905 patients, minimally invasive mitral valve surgery was associated with a mean 32 mins of additional CPB duration (P<0.01) compared to sternotomy approach (18). Even in totally endoscopic CABG (TECAB) the current trend favors implementation of CPB (19,20) rather than operating off-pump.…”
Section: Rationalementioning
confidence: 99%
“…These skills are associated with a distinct learning curve-some have suggested an estimated 75-125 procedures to attain proficiency (11,12). Patients requiring more complex repairs can be considered suitable in more experienced hands (12,13). However, by taking a standardized approach, these skills can easily be acquired and developed.…”
Section: Patient Selectionmentioning
confidence: 99%
“…This highlights the importance of preoperative vascular assessment. As such, a recently published meta-analysis reports low incidence of neurological events in peripherally cannulated patients undergoing MIMVS (13). Less commonly, some surgeons opt for central cannulation.…”
Section: Establishment Of Cpbmentioning
confidence: 99%
See 1 more Smart Citation
“…Moscarelli and colleagues compared traditional median sternotomy to a minimally invasive approach for repair of complex mitral valve disease (MVD), specifically bileaflet and Barlow's mitral valve disease. 9 They specifically examined how each approach affected the long-term outcomes of these patients by seeing if either technique was more or less likely to result in moderate mitral regurgitation (MR) or mitral valve re-operation over a period of up to 10 years. This information had previously been looked at in several single center studies at high volume centers and found no difference between the two approaches.…”
Section: Updates In Valvular Diseasementioning
confidence: 99%